(untitled) (Swiss Medical Weekly, 2014)
During the last decade, the world has witnessed numerous outbreaks of Clostridium difficile infections (CDI) in healthcare settings. Increasing incidence rates of CDI have been mainly attributed to the successful global spread of a more virulent strain of C. difficile – namely PCR-ribotype 027. More recent studies, however, point to the emergence of other ribotypes as the main cause of the continuing epidemic. This review summarises the current literature on the molecular epidemiology of C. difficile as well as its implications for clinical practice.